BUILDING A MEASURE OF CREATIVE THINKING FOR ADVANCED BASKETBALL PLAYERS - Dr. Mustafa Asaad Munshed (American Journals, 2023)
The research included four chapters, as the first chapter contained an introduction and the importance of the research. The researcher touched on the importance of creative thinking in the sports field, especially basketball. The importance of the research came in identifying the level of creative thinking among advanced basketball players,as for the problem of the research, it lies in the lack of a measure that measures the creative thinking of the advanced basketball players. As for the research fields, it included the human field, which is represented by the advanced players of Maysan Governorate for the sports season (2022-2023), and the temporal field is determined for the period from (3/15/2023). ) until (15/6/2023), while the spatial field was in the halls of the clubs of Maysan Governorate, the applicants. The researcher used the descriptive survey method, and the research sample consisted of (62) players from Maysan clubs for applicants, and the researcher built and applied the creative thinking scale, and the (SPSS) system was used to obtain the results of the research. It is acceptable in the creative thinking of advanced basketball players, so the researcher recommends that coaches pay attention to the mental aspect as it is one of the offensive requirements that affect sports performance.
Keywords: exercises, types of speed, skill abilities, youth players, basketball.